The role of the radiologist in diagnosing the COVID-19 infection. Parma experiences - Balbi, Maurizio; Ristani, Adela; Milanese , Gianluca; Silva , Mario; Ledda , Roberta Eufrasia; Milone , Francesca; Sartorio , Carlotta; Tringali , Giulia; Sverzellati, Nicola (Acta Biomedica Atenei Parmensis, 2020)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a new virus responsible for the coronavirus disease 2019 (COVID-19), a respiratory disease that ranges from an asymptomatic or mild flu-like illness to severe pneumonia, multiorgan failure, and death. Imaging might play an important role in clinical decision making by supporting rapid triage of patients with suspected COVID-19 and assessing supervening complications, such as super-added bacterial infection and thrombosis. Further studies will clarify the real impact of imaging on COVID-19 patients’ management and the potential role of radiology in future outbreaks.